2024
DOI: 10.1094/pbiomes-12-22-0107-mf
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Water Source Matters: Saline Groundwater Irrigation Lowers Date Palm Root-Associated Fungal Richness and Alters Their Community Structural Patterns

Subha Chandran,
Dinesh Sanka Loganathachetti,
Khaled Masmoudi
et al.

Abstract: Saline groundwater irrigation is commonly used in arid regions of the Middle East and North Africa for date palm (Phoenix dactylifera) cultivation, yet little is known about its impact on root-associated fungal (RAF) communities. We investigated the impact of irrigation water sources (freshwater vs. saline groundwater) on date palm RAF diversity, communities, and their assembly processes. RAF richness was lower in roots under saline groundwater irrigation and was significantly related to soil and water electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Previous research showed that irrigation with saline groundwater reduces date palm root-associated fungal abundance and amends their community structural prototypes [ 46 ]. Fungi use sporulation as an adaptation mechanism to deal with salinity [ 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that irrigation with saline groundwater reduces date palm root-associated fungal abundance and amends their community structural prototypes [ 46 ]. Fungi use sporulation as an adaptation mechanism to deal with salinity [ 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%